Investigation of Temperature and Pressure Behaviour of Constrained Lithium Ion Cell under Lithium Plating Conditions. Issue 11 (21st July 2020) - Hovestadt, L.; Wildermann, K.; Sahhary, A.; Hanke-Rauschenbach, R.
Abstract : Fast charging lithium ion cells with too high currents can cause lithium deposition at the negative electrode. To prevent this a method to determine the onset of lithium deposition based on locally resolved pressure and temperature measurements in a constrained test setup, for a given automotive lithium ion pouch cell is presented. The basic effect for pressure detection is volume increase caused by lithium deposition. For temperature measurement, the endothermic reaction behaviour of lithium deposition is exploited. An experimental study has been carried out to understand the fundamental cyclic pressure and temperature behaviour of the given cell. Additionally cell behaviour under so called lithium plating conditions is presented. Thereby inhomogeneous performance under lithium plating condition has been observed at the boundary areas. Based on experimental results an optimized fast charge protocol was developed and tested by cycling cells up to 100 cycles which shows a similar capacity retention in comparison to cycling tests with low charging current.